Aorto‐pulmonary bypass shunt for intraoperative right ventricular support during LVAD implantation. Issue 1 (28th November 2019) - Brozzi, Nicolas; Cifuentes, Renzo; Haq, Safi; Ghodsizad, Ali; Loebe, Matthias
Abstract: We describe a simple modification of the cardiopulmonary bypass (CPB) circuit that allows selective intraoperative circulatory support of the right ventricle during left ventricular assist device (LVAD) implantation. The addition of a side branch to the arterial line and an intermediate line connector allows selective venting and perfusion through a cannula inserted in the main pulmonary artery. This modification of the CPB circuit allows for selective evaluation of right ventricular function, titration of inotropic support, and early identification of patients that require right ventricular assist device (RVAD) support.